2010
DOI: 10.1186/1471-2164-11-637
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of genome architecture and gene expression reveal novel candidate virulence factors in the secretome of Phytophthora infestans

Abstract: BackgroundPhytophthora infestans is the most devastating pathogen of potato and a model organism for the oomycetes. It exhibits high evolutionary potential and rapidly adapts to host plants. The P. infestans genome experienced a repeat-driven expansion relative to the genomes of Phytophthora sojae and Phytophthora ramorum and shows a discontinuous distribution of gene density. Effector genes, such as members of the RXLR and Crinkler (CRN) families, localize to expanded, repeat-rich and gene-sparse regions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
185
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(196 citation statements)
references
References 112 publications
(145 reference statements)
7
185
1
3
Order By: Relevance
“…Moreover, Moy et al (2004) observed induced expression of a soybean (Glycine max) gene (BE584185) shortly after infection with Phytophthora sojae containing these two domains. A recent analysis from Raffaele et al (2010) focusing solely on the secretome in P. infestans corroborates our results and also concludes that proteins with BBE and FAD-linked oxidase domains are candidate virulence factors. Three genes encoding secreted metallophosphoesterases (IPR004843; PITG_20454, PITG_07720, and PITG_10322) show induced gene expression.…”
Section: Novel Candidate Domains Significantly Expanded In Plant Pathsupporting
confidence: 88%
“…Moreover, Moy et al (2004) observed induced expression of a soybean (Glycine max) gene (BE584185) shortly after infection with Phytophthora sojae containing these two domains. A recent analysis from Raffaele et al (2010) focusing solely on the secretome in P. infestans corroborates our results and also concludes that proteins with BBE and FAD-linked oxidase domains are candidate virulence factors. Three genes encoding secreted metallophosphoesterases (IPR004843; PITG_20454, PITG_07720, and PITG_10322) show induced gene expression.…”
Section: Novel Candidate Domains Significantly Expanded In Plant Pathsupporting
confidence: 88%
“…More than 50 nucleotide haplotypes were detected in 96 sequences, and the combined nucleotide diversity was 0.017 (Table 1). Effector genes are critical for the invasion, colonization, and reproduction of pathogens on hosts, and the finding of high genetic diversity in the effector gene Avr3a is consistent with the evolutionary hypothesis postulating that genes involving in antagonistic host‐pathogen coevolution have higher evolutionary rates compared to other genes as documented both in P. infestans (Cárdenas et al., 2011; de Vries et al., 2017) and many other species (Allen et al., 2004, 2008; Raffaele, Win, Cano, & Kamoun, 2010). This high evolutionary rate may well contribute to the rapid “breakdown” of many host resistances mediated by major genes (Cooke et al., 2012; Pilet et al., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Los análisis de la expresión genética de alto procesamiento por el secuenciamiento de blibliotecas de ADNc, microarreglos y la tecnología de ARNseq, son herramientas valiosas para el estudio de las diferentes familias de genes presentes en la interacción planta-patógeno (Raffaele et al 2010), por ello en el presente estudio se recurrió al uso de una de estas tecnologías. El reto de identificar genes Avr para la comprensión del patosistema papa-Phyophtora infestans en el contexto peruano es importante para el diseño de programas de diagnóstico, prevención y mejoramiento de la resistencia a P. infestans.…”
Section: Discussionunclassified
“…En el genoma de P. infestans, los genes codificantes de los efectores RXLR están presentes en las regiones dispersas que contienen los elementos transposables (TEs), que evolucionan rápidamente y sobrepasan la resistencia (Raffaele et al 2010). El silenciamiento transcripcional es otro mecanismo asociado con la ganancia de virulencia (Qutob et al 2009).…”
Section: Introductionunclassified